A study of the inhibiton of copper corrosion by triethyl phosphate and triphenyl phosphate self-assembled monolayers - HOUYI MA; SHENHAO CHEN; WENJUAN GUO (Journal of the Serbian Chemical Society, 2006)
Two kinds of phosphates, triethyl phosphate (TEP) and triphenyl phosphate (TPP), were used to form self-assembled monolayers for the inhibition of the corrosion of copper in 0.2 mol dm–3 NaCl solution. Electrochemical impedance spectroscopy (EIS) was applied to investigate the inhibition effects. The results showed that their inhibition ability first increased with increasing immersion time in ethanolic solutions of the corresponding compounds. However, when the immersion time was increased over some critical point, the inhibition effect decreased. For the same immersion time, the inhibition effect of the TPP monolayer was more pronounced than that of the TEP monolayer. Thus, ab initio calculations were used to interpret the relationship between the inhibition effects and the structures of the compounds.